2020
DOI: 10.1155/2020/6940183
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure in a Patient with Rivaroxaban-Induced Hypersensitivity Syndrome: A Case Report with a Review of the Literature and of Pharmacovigilance Registries

Abstract: Direct oral anticoagulants (DOACs) are among the most commonly prescribed medications, and DOAC-associated kidney dysfunction may be a problem that is underrecognized by clinicians. We report on the case of an 82-year-old patient who, two weeks after the prescription of rivaroxaban for atrial fibrillation, was hospitalized for a drug-induced hypersensitivity syndrome whose main clinical manifestations were low-grade fever with a petechial rash in the legs and acute renal failure (ARF). Within one week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These data are consistent with the results of recent analyses extracted from the International Pharmacovigilance Registry, which show that the reported annual rate of renal adverse events is almost 10 times higher for DOACs (7725 cases in 15 years) than for antivitamin K drugs (2145 cases reported in 50 years). According to this database, dabigatran and rivaroxaban are the drugs associated with a higher proportion of kidney-related adverse events, being 4.6% and 3.5%, respectively [ 15 ]. In the set of clinical cases of ARN, the median age of patients treated with dabigatran and rivaroxaban was 78 years.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the results of recent analyses extracted from the International Pharmacovigilance Registry, which show that the reported annual rate of renal adverse events is almost 10 times higher for DOACs (7725 cases in 15 years) than for antivitamin K drugs (2145 cases reported in 50 years). According to this database, dabigatran and rivaroxaban are the drugs associated with a higher proportion of kidney-related adverse events, being 4.6% and 3.5%, respectively [ 15 ]. In the set of clinical cases of ARN, the median age of patients treated with dabigatran and rivaroxaban was 78 years.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin-related nephropathy is a significant risk factor for the progression of CKD and mortality [15]. Many case reports have mentioned that DOACs (dabigatran, apixaban, or rivaroxaban) could also cause AKI due to the induction of tubular red blood cell (RBC) casts and tubular necrosis or interstitial nephritis [16][17][18]. Therefore, all anticoagulants cause anticoagulant-related nephropathy (ARN).…”
Section: Anticoagulant-related Nephropathymentioning
confidence: 99%
“…However, in a large study by Marcelino et al analyzing data from 134 national registries, dabigatran was associated with 4.6% of renal side effects, whereas other DOACs -rivaroxaban, apixaban and edoxaban -were shown to be related with 3.5%, 2.0% and 1.7% of renal side effects, respectively. 15 What is interesting, the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation RCT (ARISTOTLE; https://clinicaltrials.gov/, NCT00412984) showed much higher incidence of kidney damage after apixaban, reaching 13.6% of the analyzed population, despite lower incidence of major bleeding and lower mortality. 16 Due to the lack of results from other clinical trials (Renal Hemodialysis Patients Allocated Apixaban versus Warfarin in Atrial Fibrillation trial (RENAL-AF; https://clinicaltrials.gov/, NCT02942407) was prematurely terminated because of no funding and inconclusive results) 6 and possibly much higher incidence of ARN than expected, new ongoing trials regarding the safety of dabigatran…”
Section: Epidemiologymentioning
confidence: 99%
“…10 Similar observations were made by Marcelino et al, who analyzed data from the World Health Organization (WHO) pharmacovigilance program in the VigiAccess™ database. 15 The authors showed that the annual risk of renal side effects was about 2 times higher for DOAC-treated patients as compared to patients receiving VKAs, and AKI was the most commonly reported clinical finding. 15 In the available studies, most patients with ARN did not have a CKD history, had variable renal outcomes, and quite often required hemodialysis procedures; however, in most cases, kidney function improvement was observed (Table 1).…”
Section: Effect On Renal Outcome and Survivalmentioning
confidence: 99%